Effect evaluation of ecological water conveyance in Tarim River Basin, China - Jiao, Ayong; Wang, Wenqi; Ling, Hongbo; Deng, Xiaoya; Yan, Junjie; Chen, Fulong (Frontiers in Environmental Science, 2022)
Ecological water conveyance is an important way to promote the restoration of degraded ecosystems in arid watersheds. However, there are few previous research results on how to quantitatively evaluate the effect of ecological water conveyance on ecological restoration. In this regard, this paper selects the Tarim River Basin as a typical area, analyzing the changes of desert riparian vegetation and hydrological elements, constructing a watershed ecological environment quality evaluation system, and comprehensively evaluating the ecological water conveyance effect of the damaged desert forest ecosystem. The conclusion showed that the proportion of the pixel area with an upward trend of FVC from 2000 to 2021 is as high as 84.3%. The plant diversity index in the ecological water conveyance area showed the characteristics of first obvious increase and then stable. The main body of groundwater depth showed an upward trend, and the TVDI showed a downward trend of pixel area accounting for 57.0%, which indicated that ecological water conveyance had played a positive role in groundwater recharge and ecological restoration along the Tarim River. The ecological environment quality of the river basin showed a trend of transition from low-grade to high-grade, and the area with excellent ecological quality had increased from 4,635.50 km² in 2000 to 12,335.0 km² in 2021. The above research provides important scientific reference for the protection and restoration of vegetation degradation in arid watersheds.